Indian constitution - Khosla, Madhav (New Delhi Oxford, 2012)
The Indian Constitution is one of the world's great political texts. Drafted over six decades ago, its endurance and operation have fascinated and surprised many. In this short introduction, Madhav Khosla brings to light its many features, aspirations and controversies. How does the Constitution separate power between different political actors
Keywords: Constitution